Trace elements influence on bone mineral density in elderly women - Luciana Lima; Adriana C. Furtado; Ricardo Moreno Lima; Victor Machado Reis; Romulo Maia Carlos Fonseca; Ricardo Jacó de Oliveira (Desafio Singular, 2013)
To compare trace elements (TE) levels according to bone mineral density (BMD) in elderly women. 27 elderly women (65.7 ± 3.96 years) were evaluated. They were classified in two groups: high BMD (group 1) and low BMD (group 2). BMD was measured in DXA and TE were evaluated from hair sample. Higher levels of Ca, K, Na, Mo, B, Cu e Mg were found in group 1 (high BMD) while Se and Pb were higher concentrated in group 2 (low BMD). The results suggest that the imbalance in the homeostasis of ET may be a risk factor for reduced BMD and higher Pb and Se concentrations can mark bone mass loss.